Hubungan Dana Desa Terhadap Kemiskinan dan Pertumbuhan Ekonomi di Provinsi Kepulauan Bangka Belitung - Sella Agustina; Devi Valeriani; Aning Kesuma Putri (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2021)
Abstract. Poverty is one of the problems in the development process for every country in the world, especially for developing countries, namely Indonesia. One government program that aims to reduce poverty in rural areas is the village fund. Village funds are used to finance governance, development, community development and village community empowerment. Village funds are expected to reduce poverty and increase economic growth in the village. This study aims to determine the relationship and analysis of village funds with poverty and economic growth in the Bangka Belitung Islands Province. The data used are time series data for 2015-2018. The variables in this study are the Village Fund, Poverty, and Economic Growth. The type of data is quantitative data and the source of the data is secondary data. The analytical tool used is the Pearson Correlation. The results showed the relationship between village funds and poverty had a negative relationship, meaning that if village funds increased then poverty would be low and vice versa if village funds were low then poverty would increase. The relationship between village funds with economic growth has a positive relationship, meaning that if village funds increase then economic growth will increase and vice versa if village funds are low then economic growth will fall.